ISOLATION AND CHARACTERIZATION OF BIOACTIVE CONSTITUENT OF N-BUTANOL SEED EXTRACT OF Azadirachta indica - M, MUSAH; M, MOHAMMED; J. T, MATHEW; M. T., UMAR (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2022)
Extraction of the seed powdered material of Azadirachta indica followed by an extensive column chromatography of the n-butanol portion on silica gel, purification over sephadex LH20 and subsequently HPTLC resulted in to the isolation of a pale yellowish solid coded as compound MND. The isolated bioactive constituent was found to have mp of 222-224oC. The structure was elucidated using a combination of 500 MHZ and 125MHZ 1-D and 2-D NMR techniques (COSY, NOESY, HSQC, DEPT and HMBC). Thus, the isolate (MND) was determined as 4a, 7 – dihydroxy – 7 – methyl – 1 – (3, 4, 5 – trihydroxy – 6– hydro methyl – tetrahydropyran – 2 – yloxy) – 1 -, 4a, 5, 6, 7, 7a, hexahydro – cyclopenta [C] pyran – 4 – carboxylic acid methyl ester (Ipolamiide). The Antimicrobial properties of the compound MND and partition portion of the extracts were tested against S. aureus, S. pyogenes, P. vulgari, P. aeruginosa, K. pneumoniae, E. coli, S. typhi, P. digitatum, C. albicans and P. nototum. The antimicrobial sensitivity test indicated that various partition portion of the extracts inhibited the growth of S. aureus , S. pyogenes P. aeruginosa, E. coli, S. typhi, K. pneumoniaer, P. digitatum, C. albicans and P. nototum with 42mm, 38mm, 31mm, 29mm, 22mm, 30mm, 26mm, 27mm , 21 mm and 20 mm while the highest activity of the isolate (MND) was exhibited against S. aureus, P. aeruginosa, E. coli and S. typhi with 42 mm, 38 mm, 31mm and 39mm respectively.